Design, synthesis, and biological evaluation of N-arylpiperazine derivatives as interferon inducers - Chu, Yeonjeong; Reddy, B. Raja Sekhara; Gajulapalli, V. Pratap Reddy; Babu, K. Sudhakar; Kim, Eunha; Lee, Sanghee (Pergamon Press Ltd., 2020)
Type I Interferon (IFN) signaling plays an important role in the immune defense system against virus infection and in the innate immune response, thus IFNs are widely used as anti-viral agents and treatment for immune disorder or cancer. However, there is a growing demand for novel small-molecule IFN inducer due to tolerance, toxicity, or short duration of action following direct administration of IFNs. In this study, we assessed arylpiperazine (ARP) as a new core skeleton of IFN inducer. To investigate structure-activity relationship, we designed and synthesized a series of ARP analogues and evaluated the ability to stimulate IFN response in THP-1 human monocyte cells. Compound 5i was identified as a potent type I IFN inducer as it significantly increased cytokine secretion and increased expression of various IFN-stimulating genes which are representative biomarkers of type I IFN pathway. Our results suggested a beneficial therapeutic potential of 5i as an anti-viral agent.
Keywords: MULTIPLE-SCLEROSIS; HEPATITIS; DISEASES; GAMMA; BETA